Beyond BMI in Community Health Promotion: An Integrated Anthropometric, Physiological, and Functional Screening Approach among Urban Women in East Jakarta, Indonesia - Ichwan Baihaki; Taufiq Fredrik Pasiak; Afifa Radhina; Assyafiya Salwa; Bunga Anggreini Sari; Fransiskus Samuel Renaldi; Herera Rahajeng; Muhammad Fadhil; Niken Rahmah Ghanny; Ria Apriliani (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background: Community-based preventive screening is important for reducing non-communicable disease risk among adult women, particularly those who influence household health practices. However, screening activities frequently emphasize Body Mass Index (BMI), although BMI alone may not adequately describe central adiposity, elevated blood pressure, and functional health indicators. This community service article aimed to describe the implementation of health education and integrated screening involving anthropometric, physiological, and functional measurements among female guardians at Yayasan Tarbiyatul Yatim, East Jakarta, Indonesia.Aims: This study aimed to (1) implement a community-based health education and screening program for adult female participants, (2) assess anthropometric, physiological, and functional health indicators including blood pressure, BMI, waist circumference, and hand grip strength, and (3) identify the prevalence of potential cardiometabolic and functional risk markers beyond BMI.Methods: This activity was implemented on January 8, 2026 using a preventive-promotive community service framework with descriptive program evaluation. Thirty-two adult female participants joined health education, screening, and individual consultation. The community service dataset included blood pressure, pulse, oxygen saturation, body temperature, body weight, height, BMI, waist circumference, hand grip strength, health history, lifestyle profile, and current complaints. Data were analyzed descriptively using frequency, percentage, mean, median, standard deviation, and range.Result: The participants had a mean age of 49.8 years. Mean systolic and diastolic blood pressure were 129.2 mmHg and 78.8 mmHg, respectively. Mean BMI was 24.9 kg/m²; 16/32 participants (50.0%) were categorized as normal, 9/32 (28.1%) overweight, 4/32 (12.5%) obese, and 3/32 (9.4%) underweight. Mean waist circumference was 97.7 cm, and 29/32 participants (90.6%) had waist circumference >80 cm. Mean hand grip strength was 16.5 kg, and 21/32 participants (65.6%) had values <18 kg.Conclusion: Integrated screening beyond BMI is feasible in community service settings and can help identify potential cardiometabolic and functional risk indicators that require counseling or referral. Future activities should include documented repeat measurements for abnormal findings, structured pretest-posttest educational evaluation, biochemical testing, and referral follow-up.